2019
DOI: 10.46492/ijai/2019.4.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management on nutrient supply, productivity and soil fertility in Pearlmillet (Pennisetum glaucum L.)

Abstract: An experiment was conducted for 2 years (2018 and 2019) at Oilseed Research Farm, Kalyanpur, C. S. A. University of Agriculture and Technology, Kanpur, Uttar Pradesh, India to evaluate the effect of nutrient management practices on growth and yield of pearl millet (Pennisetum glaucum (L) R. Br. Emend. Stuntz.). Highest yield was observed in 5t FYM/ha application over control. Each unit increase in N level led to significant increase in growth, yield attributing characters and yield of pearlmillet. The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The results indicated that application of Poultry beat compare to other organic manure gives better result due to this number of flowers per plant, fresh weight of flower, no of branches per plant and yield per hectare found higher followed by T6, T5, T3, T4, T1, T2 and T8 respectively. [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2018b [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2015 [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2020b [3][4][5][6][7][8][9][10][11][12][13] ; Rajput et al 2020b [3,4,5] ; Rajput et al 2020a and Tomar et al 2019 [3][4]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that application of Poultry beat compare to other organic manure gives better result due to this number of flowers per plant, fresh weight of flower, no of branches per plant and yield per hectare found higher followed by T6, T5, T3, T4, T1, T2 and T8 respectively. [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2018b [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2015 [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2020b [3][4][5][6][7][8][9][10][11][12][13] ; Rajput et al 2020b [3,4,5] ; Rajput et al 2020a and Tomar et al 2019 [3][4]…”
Section: Resultsmentioning
confidence: 99%
“…The production of high value cash crops such as flowers has always been more beneficial to the farmers than the traditional crops but the marketing, post-harvest management and value addition significantly affected the income of the cultivators/farmers. Rajput et al 2020c [3,4,5] ; Tomar et al 2017 [3][4][5][6][7][8][9][10][11][12][13] ; Tomar et al 2020a and Tomar S. 2020 [3][4][5][6][7][8][9][10][11][12][13] . The major states being Karnataka Tamil Nadu, West Bengal, Andhra Pradesh and Maharastra.…”
Section: Introductionmentioning
confidence: 99%
“…181841.10). Tomar et al 2020b [31][32][33][53][54][55][56][57][58][59][60] ; Rajput et al 2020a [31][32][33] ; Rajput et al 2020b and Rajput et al 2020c [31][32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…The comparatively higher per hectare farm business income in Sugarcane-Wheat cropping system was due to higher rental value of land on which particular cropping system was followed. Tomar S. 2020 [31][32][33][53][54][55][56][57][58][59][60] ; Tomar et al 2017 [31][32][33][53][54][55][56][57][58][59][60] ; Tomar et al 2019 [31][32][33][53][54][55][56][57][58][59][60] ; Tomar et al 2020a [31][32][33][53][54][55][56][57][58][59][60] ; Tomar et al 2018a [31][32][33][53][54][55]…”
Section: Productivity and Cost Of Productionmentioning
confidence: 99%
See 1 more Smart Citation